Alphakids: butterfly garden - Feely, Jenny (Horwitz Education London, 2004)
"Butterfly Garden" is a beautifully illustrated children$1 (Bs book that invites readers into the enchanting world of butterflies and their habitats. The story follows the life cycle of a butterfly, from caterpillar to chrysalis to vibrant adult, emphasizing the wonders of transformation and growth. As readers explore the garden, they discover the different types of butterflies, their favorite flowers, and the importance of creating a welcoming environment for these delicate creatures. The book not only celebrates the beauty of nature but also encourages young readers to appreciate and protect the ecosystems that support butterflies, fostering a love for gardening and wildlife conservation.s